Invasive treatment of NSTEMI patients in German chest pain units: evidence for a treatment paradox - Schmidt, Frank Patrick; Schmitt, Claus; Hochadel, Matthias; Giannitsis, Evangelos; Darius, Harald; Maier, Lars Siegfried; Heusch, Gerd; Voigtländer, Thomas; Mudra, Harald; Gori, Tommaso; Senges, Jochen; Münzel, Thomas (International journal of cardiology, 2018)
Background:Patients with non ST-segment elevation myocardial infarction (NSTEMI) represent the largestfraction of patients with acute coronary syndrome in German Chest Pain units. Recent evidence on early vs. se-lective percutaneous coronary intervention (PCI) is ambiguous with respect to effects on mortality, myocardialinfarction (MI) and recurrent angina. With the present study we sought to investigate the prognostic impact ofPCI and its timing in German Chest Pain Unit (CPU) NSTEMI patients.Methods and results:Data from 1549 patients whose leading diagnosis was NSTEMI were retrieved from theGerman CPU registry for the interval between 3/2010 and 3/2014. Follow-up was available at median of 167 daysafter discharge. The patients were grouped into a higher (Group A) and lower risk group (Group B) according toGRACE score and additional criteria on admission. Group A had higher Killip classes, higher BNP levels, reducedEF and significant more triple vessel disease (pb0.001). Surprisingly, patients in group A less frequently receivedearly diagnostic catheterization and PCI. While conservative management did not affect prognosis in Group B,higher-risk CPU-NSTEMI patients without PCI had a significantly worse survival.Conclusions:The present results reveal a substantial treatment gap in higher-risk NSTEMI patients in GermanChest Pain Units. This treatment paradox may worsen prognosis in patients who could derive the largest benefitfrom early revascularization.
Gesehen am 30.03.2020